Muhyiddin Malas: Transition, Transplantation and Transformation - Muhammed Salman K Wayanad (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The Muhyiddin Mala, as the first text in the genre of Malappattu, not only serves as an historical exemplar marking the transition from classical Arabic forms to vernacular expressions, but also demonstrate the ‘transplantation’ process of a revered spiritual figure into a distinct socio-political environment. Typically revolving around the personality and virtues of Sheikh Abdul Qadir al-Jilani, who was the most influential Sufi figure in the whole Indian oceanic region that extends from Cairo to Java, Muhyiddin Malas draw up on the medieval tradition of tying both past and present upon to the perfect, central person of a time. This paper tries to explore some of the overlooked varieties of Muhyiddin Malas in the Keralite region, that too were of prime role in the rejuvenation of communal cohesion in the region, particularly among the Mappilas, who presumably suffered the worst part of the colonial ‘Divide and Rule' policy. The researcher tends to make use of elaborated descriptions of the historical and socio-political contexts in which the mala literature found its way to popularity, particularly against the backdrop of the repressive imperialism and divisive colonialism. The paper also tries to shed light upon how the Muhyiddin Malas & have become to influence the ordinary lifestyles and day-to-day lives of the Mappila population.